Is muscle activation diverse in females with isolated patellofemoral osteoarthritis contrasted with age-matched healthy controls during stair descent task? - Adel, Jilan; Hamoda, Reham E.; Mohamed, Ayah Mahmoud; Balbaa, Alaa Eldin; Neamat Allah, Neama H.; Hamada, Hamada Ahmed (Frontiers in Physiology, 2024)
Background: Patellofemoral osteoarthritis (PF OA) is exceptionally predominant and limiting. However, little is known about the risk factors that contribute to its onset and progression. Purpose: The aim of this study was to decide if women with PF OA descend stairs using different muscular activation strategies compared to similarly aged healthy controls. Methods: Thirty-one women with isolated PF OA and 11 similarly aged healthy women took part in this study. The activation onset and duration of PF OA in vastus medialis oblique (VMO), vastus lateralis (VL), gluteus medius (GM), transversus abdominis (TrA), and multifidus muscles were evaluated during the stair descent task using surface electromyography (EMG). Results: There was a non-significant difference between women with PF OA and healthy controls regarding all tested variables, except for the GM activation onset that was significantly delayed in women with PF OA, with the p-value of 0.011. Conclusion: The causes of PF OA differ and might not always be due to a lack of quadriceps strength or VMO activation deficiency, and prospective longitudinal studies are required to confirm this assumption.